Prevalence of allergic sensitization to storage mites in Northern Europe. Issue 3 (11th December 2019) - Jõgi, Nils Oskar; Kleppe Olsen, Robin; Svanes, Cecilie; Gislason, David; Gislason, Thorarinn; Schlünssen, Vivi; Sigsgaard, Torben; Sundbom, Fredrik; Storaas, Torgeir; Bertelsen, Randi Jacobsen
Abstract: Background: Allergic sensitization to storage mites has mostly been related to occupational exposures like farming, grain/cattle handling, whereas for non‐occupational settings, storage mite sensitization has been attributed to cross‐reactivity with house dust mite (HDM) allergens. Objective: We aimed to describe the prevalence of allergic sensitization to storage mites, co‐sensitization to HDM allergens and respiratory symptoms in Denmark, Iceland, Norway and Sweden. Methods: The population comprised of 1180 participants born 1945‐1972 of the third follow‐up of the population‐based cohort European Community Respiratory Health Survey (ECRHS) in Aarhus, Bergen, Reykjavik and Uppsala. A clinical examination included skin prick tests (SPT) to Lepidoglyphus destructor, Tyrophagus putrescentiae, Acarus siro and common inhalant allergens, as well as standardized interviews. Results: 8% were sensitized to HDM and 10% to storage mite, with some variation by study centre: Reykjavik 13%, Bergen 8% and Aarhus 7%. In Uppsala, only L destructor (3%) was measured. Storage mite sensitization was higher among men (11%) than women (8%). Among storage mite sensitized, 44% were also sensitized to HDM. Storage mite sensitization was associated with asthma and nasal allergies, but not with age, education, pet keeping or place of upbringing. Conclusions and Clinical Relevance: In this Northern European population‐based study, allergic sensitization to storage mite was as common as HDM sensitization. Storage mite sensitization was, independently of HDM sensitization, associated with respiratory symptoms and asthma. Our findings suggest that storage mite sensitization should be evaluated with regard to inclusion into the common inhalant allergen panel in Northern Europe.